1996
DOI: 10.1172/jci118506
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-10 inhibits long-term IL-6 production but not preformed mediator release from rat peritoneal mast cells.

Abstract: Mast cells have been implicated in a number of diseases involving chronic inflammation including asthma, rheumatoid arthritis, and inflammatory bowel diseases. They are a potent source of several cytokines, including IL-6 and TNF-␣ . Freshly isolated rat peritoneal mast cells will produce IL-6 in response to anti-IgE, LPS, PGE 1 , or PGE 2 ; however, the mechanisms by which such cytokine production is regulated are poorly understood. IL-10 is recognized as an important immunoregulatory cytokine with effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(90 citation statements)
references
References 42 publications
3
84
0
3
Order By: Relevance
“…A role for IL-10 in the regulation of immune responses to allergens was first suggested by studies revealing that IL-10 inhibited cytokine production by eosinophils stimulated with LPS (19). Later, it was demonstrated that IL-10 might also inhibit the production of cytokines, such as TNF and IL-6, by stimulated mast cells (20,21). IL-10 inhibits monocyte major histocompatibility complex-class (MHCclass II), B7.1 (CD80), B7.2 (CD88), intercellular adhesion molecule-1, and CD23 expression and accessory cell function (22).…”
Section: Discussionmentioning
confidence: 99%
“…A role for IL-10 in the regulation of immune responses to allergens was first suggested by studies revealing that IL-10 inhibited cytokine production by eosinophils stimulated with LPS (19). Later, it was demonstrated that IL-10 might also inhibit the production of cytokines, such as TNF and IL-6, by stimulated mast cells (20,21). IL-10 inhibits monocyte major histocompatibility complex-class (MHCclass II), B7.1 (CD80), B7.2 (CD88), intercellular adhesion molecule-1, and CD23 expression and accessory cell function (22).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage viability was determined by trypan blue exclusion as described elsewhere (Korzeniewsky & Callewaert 1983;Marshall et al 1996). Macrophage viability ranged from 89 to 97% in the different various experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Th e pro-infl ammatory mediator release may be counteracted by increased IL-10 production, which downregulates TNF-α activity, inhibits long-term IL-6 production (Marshall et al 1996, Huaux et al 1999, blocks NF-κ B activity, and is involved in the regulation of the Janus kinase/signal…”
Section: T T ő K é S Et Almentioning
confidence: 99%
“…Th e spread of pro-infl ammatory events is balanced by the release of anti-infl ammatory cytokines such as interleukin-10 (IL-10), which downregulates TNF-α activity and inhibits long-term interleukin-6 (IL-6) production (Marshall et al 1996, Huaux et al 1999. Indeed, it has been demonstrated that the TNF-α output peaks after 2 -8 h and has usually returned to the baseline by 24 h after radiation (Daigle et al 2001).…”
Section: Introductionmentioning
confidence: 99%